2013
DOI: 10.1002/imhj.21387
|View full text |Cite
|
Sign up to set email alerts
|

Beginning to “Unpack” Early Childhood Mental Health Consultation: Types of Consultation Services and Their Impact on Teachers

Abstract: ABSTRACT:The goal of the current study was to examine the impact of the frequency of two types of early childhood mental health consultation (ECMHC) activities (time spent in the class and time spent meeting with teachers) on teacher-child interactions, use of positive classroom-management techniques, and the intent to quit the childcare profession. We addressed these questions with a sample of 115 teachers from private childcare settings participating in a midlength (6-8 months) consultation partnership, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Arkansas' ECMHC program, Project PLAY (Positive Learning for Arkansas' Youngest), has sought to draw attention to the need to support young foster children in their child care settings. State‐level data suggest that most foster children are placed in child care centers that are not quality rated and that they have frequent disruptions to their care (Conners‐Burrow et al, ). While assisting state partners in designing training and policy solutions to this problem, the Project PLAY team began prioritizing ECMHC services to child care programs in which foster children are enrolled.…”
Section: Ecmhc For Children In Foster Carementioning
confidence: 99%
See 1 more Smart Citation
“…Arkansas' ECMHC program, Project PLAY (Positive Learning for Arkansas' Youngest), has sought to draw attention to the need to support young foster children in their child care settings. State‐level data suggest that most foster children are placed in child care centers that are not quality rated and that they have frequent disruptions to their care (Conners‐Burrow et al, ). While assisting state partners in designing training and policy solutions to this problem, the Project PLAY team began prioritizing ECMHC services to child care programs in which foster children are enrolled.…”
Section: Ecmhc For Children In Foster Carementioning
confidence: 99%
“…Results from multiple evaluations of Project PLAY suggest the program is having success in improving the child care experience for young children (Conners‐Burrow et al, ; Conners‐Burrow, Whiteside‐Mansell, McKelvey, Vermani, & Sockwell, ). The most recent evaluation report includes data collected since Project PLAY began to prioritize services to child care centers that serve young foster children.…”
Section: Ecmhc For Children In Foster Carementioning
confidence: 99%
“…In a childcare setting, there are several steps in this child-centered consultation process (Conners-Burrow et al, 2013). Initially, the ECMH consultant collaborates with the team to gather pertinent information and assessment data.…”
Section: What Are the Various Components Of Child-centered Consultation In A Childcare Classroom?mentioning
confidence: 99%
“…Open communication and positive relationships are vitally important and influence the degree to which the consultation and implementation process is successful (Carlson et al, 2012). For example, research has shown that an increase in the frequency of meetings between an ECMH consultant and teacher results in more positive teacher–child interactions (Virmani et al, 2013), and the amount of time an ECMH consultant spends in the classroom directly affects the perceived benefits from the teacher’s perspective (Conners-Burrow et al, 2013).…”
Section: Is a Collaborative Team Approach Really Necessary?mentioning
confidence: 99%
See 1 more Smart Citation